2019
DOI: 10.1063/1.5115588
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition characteristics of C4F7N/CO2 mixture under AC discharge breakdown

Abstract: Recently, the C4F7N/CO2 mixture has been highly considered as a promising SF6 alternative due to its low greenhouse effect and excellent electrical performance. Apart from its dielectric strength and arc-quenching capability, the decomposition characteristics of C4F7N/CO2 also play an important role in its future applications in gas-insulated electrical equipment. Therefore, decomposition experiments of the C4F7N/CO2 mixture were carried out under multiple AC discharge breakdowns by using a needle-to-plate ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 26 publications
4
43
0
Order By: Relevance
“…The high reactivity of CN group probably results in the interaction between C4F7N molecules and metallic heating elements under high temperature to generate C3F7 and CN particles (shown in Table 4 (D1)). C3F7 particles could combine with F particles to form C3F8 (shown in Table 4 (R3)) or be decomposed to generate C3F6, which is also confirmed by the previous research on the compatibility between C4F7N/CO2 and metal [19]. The gas by-product C3F6 was firstly detected at 220°C during the gas-solid interface reaction [19].…”
Section: Csupporting
confidence: 78%
See 1 more Smart Citation
“…The high reactivity of CN group probably results in the interaction between C4F7N molecules and metallic heating elements under high temperature to generate C3F7 and CN particles (shown in Table 4 (D1)). C3F7 particles could combine with F particles to form C3F8 (shown in Table 4 (R3)) or be decomposed to generate C3F6, which is also confirmed by the previous research on the compatibility between C4F7N/CO2 and metal [19]. The gas by-product C3F6 was firstly detected at 220°C during the gas-solid interface reaction [19].…”
Section: Csupporting
confidence: 78%
“…C3F7 particles could combine with F particles to form C3F8 (shown in Table 4 (R3)) or be decomposed to generate C3F6, which is also confirmed by the previous research on the compatibility between C4F7N/CO2 and metal [19]. The gas by-product C3F6 was firstly detected at 220°C during the gas-solid interface reaction [19]. Therefore, the yield of C3F6 and C3F8 is higher than CF4 under POF decomposition conditions.…”
Section: Csupporting
confidence: 76%
“…For a 4% Novec TM 4710/96% CO 2 , the equivalence with SF 6 at 5.5, 6.5, 7.5 bar abs are feasible for a minimum operating temperature of −30 • C, −25 • C, and −20 • C [1][2][3][4], respectively. Novec TM 4710 (C 4 F 7 N)/CO 2 mixtures consist of complex molecules, formed from several basic elements (5 Carbons,7 Fluorines, 2 Oxygens, and 1 Nitrogen), the energy absorption by the constituents of these mixtures causes their fragmentation into smaller radicals, that are more stable [5][6][7]. Once at rest, unlike SF 6 , the decomposition products do not recombine to the original chemical arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…After 2000 times of breakdown tests, the content of CO is the highest. At the same time, layer of pale yellow powdery solid can be found on the cavity wall and electrode surface, and its main components are Cu, F, N and Si [42]. Comparing the AC discharge breakdown with the corona discharge, it can be found that the short carbon chain products are easier to form under the AC discharge breakdown condition, while the long carbon chain products are dominant under the corona discharge condition.…”
Section: Gas Decomposition Properties and Compatibility With Solid mentioning
confidence: 99%